Qualitative research theory, method and practice - Silverman, David (London Sage, 2004)
Common themes in this volume include the centrality of the relationship between analytic perspectives and methodological issues, links between social science traditions, and the need to expand the paradigm of qualitative research.
Introducing qualitative research / David Silverman -- Ethnography : relating the part to the whole / Isabelle Baszanger and Nicolas Dodier -- Building bridges : the possibility of analytic dialogue between ethnography, conversation analysis and Foucault / Gale Miller and Kathryn J. Fox -- Analysing documentary realities / Paul Atkinson and Amanda Coffey -- Doing things with documents / Lindsay Prior -- Internet communication as a tool for qualitative research / Annette N. Markham -- The "inside" and the "outside" : finding realities in interviews / Jody Miller and Barry Glassner -- The active interview / James A. Holstein and Jaber F. Gubrium -- Membership categorization and interview accounts / Carolyn Baker -- Focus group research / Sue Wilkinson -- Discourse analysis as a way of analysing naturally occurring talk / Jonathan Potter -- Conversation analysis and institutional talk : analysing data / John Heritage -- The conceptualization and analysis of visual data / Michael Emmison -- Analysing lace-to-face interaction : video, the visual and material / Christian Heath -- Reliability and validity in research based on naturally occurring social interaction / Anssi Peräkylä -- Addressing social problems through qualitative research / Michael Bloor -- Using qualitative data and analysis : reflections on organizational research / Gale Miller, Robert Dingwall and Elizabeth Murphy -- Who cares about 'experience'? Missing issues in qualitative research / David Silverman.
PI-8274 donated by Department of Global Development Cornell University Ithaca.
Keywords: Social sciences -- Research; Discourse analysis